Effects of Combined Anisodamine and Neostigmine Treatment on the Inflammatory Response and Liver Regeneration of Obstructive Jaundice Rats after Hepatectomy - Li, Chong-Hui (Biomed Res Int, 2014)
Background. Cholestasis is associated with high rates of morbidity and mortality in patients undergoing major liver resection. This study aimed to evaluate the effects of a combined anisodamine and neostigmine (Ani+Neo) treatment on the inflammatory response and liver regeneration in rats with obstructive jaundice (OJ) after partial hepatectomy. Materials and Methods. OJ was induced in the rats by bile duct ligation. After 7 days biliary drainage and partial hepatectomy were performed. These rats were assigned to a saline group or an Ani+Neo treatment group. The expressions of inflammatory mediators, liver regeneration, and liver damage were assessed at 48 h after hepatectomy. Results. The mRNA levels of TNF-α, IL-1β, IL-6, MCP-1, and MIP-1α, in the remnant livers, and the serum levels of TNF-α and IL-1β were substantially reduced in the Ani+Neo group compared with saline group (P < 0.05). The Ani+Neo treatment obviously promoted liver regeneration as indicated by the liver weights and Ki-67 labeling index (P < 0.05). The serum albumin and γ-GT levels and liver neutrophil infiltration also significantly improved in the Ani+Neo group (P < 0.05) compared with the saline group. Conclusions. These results demonstrate that the combined anisodamine and neostigmine treatment is able to improve the liver regeneration in rats with OJ by substantially alleviating the inflammatory response.